SCIENTIFIC LEARNING APPLICATIONS IN READING ACTIVITY OF NARRATIVE TEXT TO IMPROVE POSITIVE PARTICIPATION OF STUDENTS IN CLASS IX-1 AT SMP NEGERI 1 PADANGSIDIMPUAN - agusrin sikumbang (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This classroom action research was conducted to find out how the application of learning science in learning to read narrative texts is able to increase students' positive participation in learning English in Class IX-1 at SMP Negeri 1 Padangsidimpuan. This qualitative research was carried out in two research cycles with 24 students as participants and the researcher himself as participant-observer. The technique of collecting data is through observation and analysis of findings, and the findings are then analyzed qualitatively based on relevant theories. This study proves that the implementation of learning with the application of a scientific approach in learning English is able to increase students' positive participation in participating in Fairy Tale reading learning activities in Class IX-1 at SMP Negeri 1 Padangsidimpuan. The ability of students in group cooperation is strongly influenced by the heterogeneity of group members. The scientific approach directs students to be more confident in asking questions, expressing opinions properly and correctly, being able to find information in an orderly manner and making responsible presentations. Teachers who implement the scientific approach should not only act as information providers in learning activities, but teachers must also be able to act as motivators, collaborators, inspirations and good models to develop and foster positive characters in students. Further research in relation to the above themes still needs to be done to obtain more satisfactory results.